Eksistensi Polisi Cepek Sebagai Representasi Pahlawan Jalanan Di Daerah Kampus Kota Jember - Anisa Andiana W. S; Hana Vernanda; Lisa Roselawati (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The phenomenon of polisi cepek has spread to almost every intersection in the city, coinciding with the increasing volume of vehicles, especially in campus areas. Polisi cepek is interpreted as a figure that regulates traffic similar to traffic lights scattered throughout the city. The presence of polisi cepek in Jember City can be observed at busy intersections, such as the intersection of Kaliurang Street and Jawa Street around the University of Jember. James S. Coleman's perspective on rational choice theory serves as the theoretical foundation for observing the social phenomenon of polisi cepek. This research employs a qualitative method with techniques including interviews, field observations, and literature reviews. The aim of the study is to understand the factors that rationalize an individual's choice to work as polisi cepek, beyond economic considerations. The research findings indicate that the motivation for individuals to engage in this profession is not solely based on economic necessities for survival; rather, empathy plays a significant role in the background of this social phenomenon. The humanitarian aspect within individuals serves as a driving force to take action by utilizing the resources at their disposal.